A novel comparator - a cryptographic design in quantum dot cellular automata. (19th March 2020) - Qadri, S. Umira R.; Bangi, Z.A.; Banday, M. Tariq; Bhat, G. Mohiuddin; Beigh, M. Rafiq
Quantum-dot cellular automata (QCA), an advanced nanotechnology, is a branch of nano-electronics that attempts to create general computation at nano scale by controlling the position of electrons. The basic logic in QCA does not use voltage level for logic representation; rather it represents the binary state by polarisation of electrons in the quantum cell, which is basic building block of QCA. QCA technology has large potential to provide high space density, ultra-low power dissipation that enables us to build QCA circuits with faster speed, smaller size and high performance for integration and computation. QCA presents proficient solutions for several arithmetic circuits, such as adders, multipliers, comparators etc. This paper presents a thorough analysis of QCA-based universal FNZ gate (Khanday et al., 2013) with its stability proof upon which a new design of 1-bit comparator has been proposed. The proposed work uses novel implementation strategies, methodologies and new formulations of basic logic equations to make the proposed designs more efficient in terms of cell count, area, polarisation etc. The functionality of universal FNZ gate based 1-bit comparator has been tested by QCA designer where a comprehensive comparison with the formerly reported designs confirm the consistent performance and high efficiency of the proposed designs.